2012
DOI: 10.1074/jbc.m112.358853
|View full text |Cite
|
Sign up to set email alerts
|

Stable IL-2 Decision Making by Endogenous c-Fos Amounts in Peripheral Memory T-helper Cells

Abstract: Background: The precise fine-tuning of IL-2 expression is crucial for the immune system. Results: Endogenous expression levels of c-Fos and NFATc2, but not of c-Jun and NF-Bp65, are limiting for IL-2 decision making. Conclusion: Variation in the physiological c-Fos expression leads to diversity and robustness in IL-2 response within the population. Significance: The approach used is beneficial for uncovering basic mechanisms during gene regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 44 publications
(20 reference statements)
3
13
1
Order By: Relevance
“…Recently, we confirmed that U0126 does not inhibit the expression of NFATc2, c-Jun, and NF-κBp65 under the conditions used (Bendfeldt et al, 2012). U0126 inhibits de novo synthesis of c-Fos after T cell stimulation in a dose-dependent manner (Figure 7, upper part).…”
Section: Resultssupporting
confidence: 74%
“…Recently, we confirmed that U0126 does not inhibit the expression of NFATc2, c-Jun, and NF-κBp65 under the conditions used (Bendfeldt et al, 2012). U0126 inhibits de novo synthesis of c-Fos after T cell stimulation in a dose-dependent manner (Figure 7, upper part).…”
Section: Resultssupporting
confidence: 74%
“…For intracellular staining of the transcription factors NFATc2 (Cy5-labeled own polyclonal antibodies (Bendfeldt et al, 2012), c-Fos (Alexa Fluor 488-labeled rabbit polyclonal IgG antibodies from Santa Cruz Biotechnology, RRID:AB_2231996), and Foxp3 (PE-Cy7-labeled antibody clone FJK-16s from eBioscience, RRID:AB_891554) the cells were stained with 1.34 µM Pacific Orange succinimidyl ester to exclude dead cells, fixed with Foxp3 fixation buffer (eBioscience), stained in Foxp3 permeabilization buffer (eBioscience), and analyzed using a LSR II flow cytometer (BD Biosciences). Data were analyzed with FlowJo software (Treestar, Ashland, OR).…”
Section: Methodsmentioning
confidence: 99%
“…There are a number of in vitro studies, some of them even combined with mathematical modeling, to dissect the dichotomic effect of IL-2 signaling in effector Th cells and Foxp3 + Treg cells (Benary et al, 2008; Bendfeldt et al, 2012; Busse et al, 2010; Feinerman et al, 2010; Tkach et al, 2014; Voisinne et al, 2015). Observations from various knock-out mice (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are corroborated by a previous report showing that a specific MEK (MAP kinase/extracellular signal-regulated kinase) 1/2 inhibitor (upstream of c-Fos), U0126, inhibited de novo synthesis of c-Fos after T cell stimulation. As a result, the frequency of IL-2 producing cells was reduced within the human memory Th population, whereas the NFATc2 expression level remained unaffected (30). Based on our in vitro studies, we hypothesized that the suppression of alloreactive T cell responses by inhibiting cFos/AP-1 using T-5224 could contribute to preventing allogeneic rejection in PIT models.…”
Section: Discussionmentioning
confidence: 92%